Study On The Work Life Balance Of Supervisors In Hotels - Paresh Bali, Dr Manohar Sajnani, Dr R K Gupta (International Journal of Advanced Science and Technology, 2020)
The aim of the study was to identify the levels of work life balance (WLB) of supervisors working in different departments of the hotels and to analyze levels of WLB with respect to factors like genders, marital status and family structure. Supervisors are defined as the front line managers who control and monitor day to day functioning and act as link between staff, customers and management. As the work characteristics of hotel is every challenging and difficult, achieving a good balance of work and life is always difficult and is more applicable in case of supervisors. Personal factors like gender, marital status, family structure may also have a decisive effect on the levels of WLB experienced by an individual. The main aims of the study were to measure the levels of work life balance experienced by supervisors and its association with factors like gender, marital status and differential family structure. The information required for the study was collected by author with the help of a questionnaire developed for the purpose. Based on the explorative study four dimensions were identified to measure the levels of work life balance experienced by an individual. The scores were calculated on these dimensions to estimate the levels of work life balance. Study employed various statistical procedure to test the reliability and validity of the instrument and to analyze the collected information. The values for Cronbach alpha was over and above 0.865 and coefficient of correlations were also proved the reliability for the questionnaire. The results had shown that there is a lack of satisfactory levels of work life balance for supervisors. The result indicates that WLB for supervisors those were single were greater than supervisors who were married. As per the analysis female supervisor reported to have better WLB in comparison male supervisors. The work life balance levels of supervisors with children requiring parental care were found to be lower as compared to employees with either no children or with grown up children with lesser parental care. The work life balance levels were better for supervisors who do not live with parents as compared to supervisors who live with their parents requiring care.